WormFarm: a quantitative control and measurement device toward automated Caenorhabditis elegans aging analysis. Issue 3 (27th March 2013) - Xian, Bo; Shen, Jie; Chen, Weiyang; Sun, Na; Qiao, Nan; Jiang, Dongqing; Yu, Tao; Men, Yongfan; Han, Zhijun; Pang, Yuhong; Kaeberlein, Matt; Huang, Yanyi; et al.
Summary Caenorhabditis elegans is a leading model organism for studying the basic mechanisms of aging. Progress has been limited, however, by the lack of an automated system for quantitative analysis of longevity and mean lifespan. To address this barrier, we developed 'WormFarm', an integrated microfluidic device for culturing nematodes. Cohorts of 30–50 animals are maintained throughout their lifespan in each of eight separate chambers on a single WormFarm polydimethylsiloxane chip. Design features allow for automated removal of progeny and efficient control of environmental conditions. In addition, we have developed computational algorithms for automated analysis of video footage to quantitate survival and other phenotypes, such as body size and motility. As proof‐of‐principle, we show here that WormFarm successfully recapitulates survival data obtained from a standard plate‐based assay for both RNAi‐mediated and dietary‐induced changes in lifespan. Further, using a fluorescent reporter in conjunction with WormFarm, we report an age‐associated decrease in fluorescent intensity of GFP in transgenic worms expressing GFP tagged with a mitochondrial import signal under the control of the myo‐3 promoter. This marker may therefore serve as a useful biomarker of biological age and aging rate.